A Sustainability-Oriented TOPSIS Framework for Supplier Evaluation and Selection - Rahman, Md Saifur; Hoque, A.S.M. Tariq; Ali, Md. Hasan; Md Rafiquzzaman (Journal of Technology Management and Business, 2026)
Supplier selection plays a vital role in enhancing the efficiency and competitiveness of supply chain management (SCM). Selecting the most appropriate supplier mitigates procurement risk, enhances product quality, and guarantees timely delivery. This study establishes a Multi-Criteria Decision-Making (MCDM) framework based on the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to assess and identify the most appropriate plastic raw material supplier for RFL Group. Four supplier alternatives from China were assessed using eleven criteria covering operational, economic, relational, and environmental dimensions, including lead time, reliability, carbon emission rate, quality of raw material, response time, return ability, warranties and claims policies, geographical location, and quantity discount. The criteria were selected based on supplier-selection literature, organizational procurement requirements, and expert judgment. The criterion weights were determined using an expert-based weighting procedure and then applied in the TOPSIS calculation. The results show that Shandong Liangshan Quanxing Plastics Co., Ltd. achieved the highest relative closeness (C_i^*=0.6695). Sensitivity analysis using ±10% changes in key criterion weights confirmed the stability of the final ranking. Comparative AHP-rating synthesis also selected supplier S as the strongest alternative. The study contributes by integrating sustainability-related evaluation, particularly carbon emission rate, into a transparent TOPSIS-based supplier-selection model and by demonstrating how MCDM can support practical procurement decision-making in the plastic manufacturing sector.